3- Recherche Economique et Système Mondial Capitaliste Le Tiers Monde et l’Instrumentalisation de la Recherche - F. Yachir (Africa Development, 1978)
In a system where academic knowledge is sub-divided, Economics has achieved pride of place in Social Science Research. The interna tionalisation of capital has given birth to a world system of economic research, with all the inequalities inherent in the capitalist system. Within the Third World, Economic research goes through a process of dependent integration in the International division of scientific labour, thus reproducing the dependent statuts of these countries in the impe rialist system : the division between « producers » and « consumers » of concepts. What is lacking in social science research in the Third World is not so much applied research as the development of this research on the basis of alternative theories of development, and the reason for this may be found basically in the relationship between theoretical production and a social formation with its structure, its class relations, etc. The historical development of economic theory follows very closely the historical development of capital and the serious crises of this theory coincide with the great upheavals of instability of the capitalist system. Ricardo refers to the rising bourgeoisie, Walras to the triumphant bourgeoisie and Keynes to interventionist bourgeoisie. Similarly the integration of the Third World in the world capitalist system explains its place in the predominant economic theory with the import of ready made neo Classical or Keynesian conceptual categories and the acceptance of the universality of its analytical methods. In other words, the fundamental question for the Third World which is precisely its integration in the world capitalist system cannot be answered by an economic theory which is used for its domination. Nor would an « import-substitution » and applied economic research be helpful, for this is only a form of the international division of labour in scientific activity, with a very narrow specialization for the Third World limited to the study of the most partial and immediate aspects of development and underdevelopment in their region. The author advocates the creation of conditions for a complete divorce between the dependent societies and the world system which established their dependency. An alternative theory of development must take into account the scientific theory of capitalism as was done by Marx and develop an original approach to the specific forum of capitalist development in Africa, Asia and Latin-America Applied economic research must be redirected towards an understanding of the complex processes of transition to socialism. Finally there must be a different social distribution of scientific activity with regard to the organization of research, greater efficiency arid consumption of the fruits of this rese